Systematic Literature Review: Analysis of the Impact of Self-Efficacy Application on Assessment of Organizational Commitment and Employee Performance at PT. Samudera Perdana Selaras - Fu’adah, Tsamroatul; Afidah, Azizatul; Akbar, Mokhammad Ramadani Ilham; Jumiati, Merri; Putra, Riyan Sisiawan (GREENOMIKA, 2023)
This study aims to examine the impact of implementing self-efficacy on the assessment of organizational commitment and employee performance. The method used in this research is systematic literature review, which involves collecting data and information from literature sources such as journals, internet articles, and other related literature. This research refers to relevant previous research to gain an in-depth understanding of the impact that occurs on the topics discussed. The results of this study indicate that self-efficacy affects organizational commitment at PT Samudera Perdana Selaras. In addition, self-efficacy also affects employee performance at PT Samudera Perdana Selaras. Therefore, it can be concluded that self-efficacy plays an important role in improving organizational commitment and employee performance at PT Samudera Perdana Selaras.